286 Disparities in the Management of Low-Risk Febrile Infants: An Interim Feasibility Report. (April 2022) - Gutman, Colleen K; Aronson, Paul; Lion, K. Casey; Fisher, Carla; Patterson, Mary; Fernandez, Rosemarie
Abstract : OBJECTIVES/GOALS: Well-appearing febrile infants are a model for exploring communication, bias, and health disparities in the pediatric emergency department (ED). Using mixed methods, we will perform an in-depth analysis of disparities and shared decision making, a potentially modifiable driver of inequities. METHODS/STUDY POPULATION: We will conduct a multicenter cross-sectional chart review study of well-appearing febrile infants 29-60 days old treated in the ED and apply multivariable logistic regression to assess the association between 1) race/ethnicity and 2) limited English proficiency with the primary outcome, discharge to home without lumbar puncture and without antibiotics (standard of care). We will concurrently perform an interpretive study using purposive sampling to conduct interviews with: 1) minority parents of febrile infants and 2) ED physicians. By capturing dyadic data, we will triangulate perspectives to elucidate disparities and bias that can emerge in the shared decision making process. RESULTS/ANTICIPATED RESULTS: Forty member institutions of the Pediatric Emergency Medicine Collaborative Research Committee are participating, providing a projected cohort of 3000 infants. In the 6 months since site recruitment, 235 eligible infants have been entered into the dataset (43% minority race/ethnicity, 6% language other than English), 61% of whom received the primary outcome. Chart review has the benefits of 1) ensuring exclusion of ill infants, 2) providing data on interpreter use that is unavailable in administrative datasets, and 3) allowing an analysis of shared decision making. These findings will inform an interpretive study of parent and provider experiences of bias in shared decision making. DISCUSSION/SIGNIFICANCE: We demonstrate the feasibility of a large-scale manual chart review to analyze disparities within a shared decision making context. Partnered with qualitative scholarship, this research will support the development of communication interventions to mitigate implicit bias in the clinical encounter.